A small-flowered natural Odontoglossum hybrid (Orchidaceae: Oncidiinae) from Ecuador - Dalström, Stig (Universidad de Costa Rica, 2019)
A new small-flowered natural Odontoglossum hybrid from northwestern Ecuador is described and illustrated with a line drawing and a photograph. The novelty is compared with its sympatric parent species, Odontoglossum armatum and O. mirandum. The flower of the new natural hybrid has shorter erect lateral lip-lobes compared to those for O. mirandum, but distinctly longer erect lateral lip-lobes compared to those for O. armatum, which are basically lacking altogether. The taxonomic status of the variable O. mirandum is briefly discussed.